Gauss-type integral inequalities for interval and fuzzy-interval-valued functions - Costa, T. M.; Silva, G. N. [UNESP]; Chalco-Cano, Y.; Roman-Flores, H. (Springer, 2019)
This study presents new Gauss's inequalities for interval and fuzzy-interval-valued functions using the Aumann's and Kaleva's improper integrals. The inequality for interval-valued functions is based on the Kulisch-Miranker order relation. The order relation given in the fuzzy-interval space is defined level-wise through the Kulisch-Miranker order, and by means of this the inequality for fuzzy-interval-valued functions is interpreted.
Keywords: Gauss' inequality; Interval-valued functions; Fuzzy-interval-valued functions